Building a Mathematical Equation for Describing Volume Changes in Suction and Pumping Chambers of an Improved Type of the Roots Blower - Trinh, Dong Tinh; Tran, Ngoc Tien; Nguyen, Hong Thai (Old Journal, 2020)
The volume change in suction and pumping chambers of the roots type of hydraulic devices is an important factor deciding machine performance. This volume change creates suction and pumping pressures when the machine is working. Therefore, when designing and optimizing design of the machine, it is necessary to build a mathematical model for describing those changes in relation with rotation angle of the driving shaft. To reach this goal, the authors carry out volume modelling process by building mathematical model for calculating the volume changes of the area of the suction/pumping chambers in relation with rotation angle of the driving shaft of the specific type of Roots pump, which has been proposed by the authors. In addition, this study also points out that when the designing parameter such as the ratio parameter between ellipse's shorter axis and its larger axis changes from 1 to 0.5, the volume change gradually increases and reaches 26.77% when the design parameter equals to 0.5.